Mississauga: Heritage Management in an Ordinary Place - McIlwraith, Thomas (Urban History Review / Revue d'histoire urbaine, 1985)
The management of the built resources in a city dominated by large numbers of ordinary structures and few landmarks of the traditional sort presents special challenges. When structures do not speak for themselves, citizens may be assisted by appropriate labelling, a procedure which can get out of control as the features which might be recognized are almost without limit. The city of Mississauga is used to illustrate the vital need for a heritage strategy in such places, and how such a strategy might be beneficial to broad city interests.